Comparative analysis of organelle genomes provides conflicting evidence between morphological similarity and phylogenetic relationship in diatoms - Jeong, YuJin; Lee, JunMo (Frontiers in Marine Science, 2024)
Diatoms (Bacillariophyta) are abundant phytoplankton groups in marine environments, which contribute approximately 20% of global carbon fixation through photosynthesis. Moreover, diatoms exhibit the highest species diversity (approximately 18,000 diatom species) among marine photosynthetic eukaryotes, which were identified by morphological characteristics. Molecular phylogenetic analyses could shed new insights into the evolutionary relationships of diverse diatom species. Nevertheless, a comprehensive understanding of the phylogenetic relationships of diatom species still remains unclear because the available molecular data are insufficient compared with their high species diversity. Furthermore, several novel diatom species were reported from field samples with no molecular evidence. In particular, the phylogenies of diatom species constructed using organelle genomes revealed that several diatom genera are paraphyletic with high supporting values. We constructed high-resolution phylogenetic trees of diatom species using organelle genomes (plastids and mitochondria) and compared the morphologies in several paraphyletic diatom genera. Especially, the clades Nitzschia and Thalassiosira include several different diatom genera with high phylogenetic supports. Our study demonstrated that some morphological characteristics (e.g., genus characters) of several diatom genera could not represent current genus boundaries. Based on the results, we highlight the necessity for taxonomic reinvestigation. To reestablish this in diatoms, it will be essential to incorporate more genome data from a broader range of taxon samples, along with a comparison of morphological characteristics.